WHAT ARE STUDENTS’ LEVELS OF COMMUNICATION AND COLLABORATION SKILLS THROUGH PROBLEM-SOLVING LEARNING? - Muhajir, Siti Nurdianti (Journal of Teaching and Learning Physics, 2023)
This study aims to analyze the collaboration and communication skills of Madrasah Aliyah students in physics. This research was conducted in one of the private Madrasah Aliyah in Garut Regency with the method used as a descriptive quantitative method. The sample in this study was 15 students of class XI IPA who were selected by random sampling technique. The instruments used in this study were observation sheets, a questionnaire of peer assessment and self-assessment questions adapted to indicators of collaboration and communication skills from the P21 Buck Institute of Education in problem solving learning activities. The findings show significant data differences between the results of peer and student self-assessments which are then analyzed in more depth with teacher observation data as a comparison. Based on the results of the analysis of the main factors that influence students' collaboration and communication skills are the level of self-confidence and students' reading habits.